2011
DOI: 10.1097/aog.0b013e3182172c82
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Interval for Ultrasound Surveillance in Monochorionic Twin Gestations

Abstract: fusion syndrome group (20.3Ϯ4.1 and 23.3Ϯ4 .0 weeks of gestation, Pϭ.047 and .049 by unpaired t test).Our data indicate that the development of twin-twin transfusion syndrome is fast, and the gestational age at diagnosis of late-stage twin-twin transfusion syndrome tends to be earlier than that of early-stage twin-twin transfusion syndrome with an ultrasound interval of 14 days or less.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 4 publications
0
20
0
Order By: Relevance
“…This prevalence is less than half that of previous reports including the typical onset of TTTS during the second trimester [1,9,15]. Thorson et al reported five cases that were diagnosed after 28 weeks among 42 TTTS pregnancies (12%) [25]; however, that series consisted of patients referred from a number of hospitals at an unspecified stage of gestation.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…This prevalence is less than half that of previous reports including the typical onset of TTTS during the second trimester [1,9,15]. Thorson et al reported five cases that were diagnosed after 28 weeks among 42 TTTS pregnancies (12%) [25]; however, that series consisted of patients referred from a number of hospitals at an unspecified stage of gestation.…”
Section: Discussionmentioning
confidence: 87%
“…Twin-twin transfusion syndrome (TTTS) occurs at a frequency of 8%-10% in monochorionic twin pregnancies [1,9,15], and the majority of those cases are diagnosed during the second trimester [25]. In the last two decades, the overall prognosis of TTTS cases diagnosed before 26 weeks of gestation has dramatically improved by the introduction of fetoscopic laser photocoagulation (FLP) for placental communicating vessels [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Thorson et al 9 found a significant increase in the diagnosis of late‐stage twin‐twin transfusion syndrome (stages III–IV) with a sonographic surveillance interval of greater than 14 days. They noted that with a sonographic surveillance interval of 14 days or less, 13.3% of twin‐twin transfusion syndrome cases were diagnosed at advanced stages, whereas with a surveillance interval of greater than 14 days, 59.3% of cases were advanced.…”
Section: Discussionmentioning
confidence: 99%
“…Because randomized studies of the optimal surveillance of monochorionic pregnancies are not published, the 2-week interval of ultrasound surveillance from at least 16 weeks of gestation until delivery is based on available literature and expert opinion. 7,17,18 Additionally, a complete fetal anatomical survey is recommended at 18-22 weeks of gestation, which should be performed based on current guidelines. 19,20 …”
Section: Initiation Timing and Duration Of Surveillancementioning
confidence: 99%